Abiraterone or Enzalutamide in Advanced Castration‐Resistant Prostate Cancer: An Indirect Comparison. Issue 6 (19th January 2017) - Chopra, Akhil; Georgieva, Mina; Lopes, Gilberto; Yeo, Chong Ming; Haaland, Benjamin
Abstract : BACKGROUND: To perform a comparative effectiveness analyses between enzalutamide and abiraterone acetate in both the pre‐docetaxel and post‐docetaxel settings based on published phase III randomized trials. METHODS: The primary measure of efficacy was the posterior probability that enzalutamide outperforms abiraterone acetate (AA) with prednisone in terms of overall survival (OS) on average. Indirect meta‐estimates were generated from four randomized studies in the context of a Bayesian hierarchical model with study‐specific efficacy estimates meta‐analyzed on the log scale. RESULTS: We found weak evidence that enzalutamide outperforms AA with prednisone in terms of OS in the pre‐docetaxel and post‐docetaxel settings. However, we found strong evidence that enzalutamide outperforms AA with prednisone in terms of radiographic PFS, time until PSA progression, and PSA response rate in both the pre‐ and post‐docetaxel settings. Rates of grade 3 or worse adverse events were broadly similar between treatment (enzalutamide or AA) and control arms (placebo or placebo with prednisone) in all included randomized studies. CONCLUSIONS: There is strong evidence that enzalutamide outperforms AA with prednisone in terms of radiographic PFS and PSA progression and PSA response rate but not OS in the pre and post‐docetaxel settings. These results may further guide clinicians in making treatment recommendations for patients with advanced prostate cancer. Prostate 77: 639–646, 2017 . © 2017 Wiley Periodicals, Inc.